A flexible and effective NC machining process reuse approach for similar subparts. (May 2015) - Huang, Rui; Zhang, Shusheng; Xu, Changhong; Zhang, Ximao; Zhang, Congcong
Abstract: NC machining process reuse is widely accepted as an effective strategy for engineers to generate the process plan with less time and lower cost. However, there has been very little research on how to reuse the NC machining process of similar subparts. As a result, most reusable NC machining process still has to remain in the repository as tacit knowledge, which can easily get lost due to oblivion. This paper proposes a novel NC machining process reuse approach for similar subparts in which existing NC machining process cases are described in association with machining features. First, a feature-based parameter-driven model is established to formalize the links between information imbedded in the machining feature and the parameters of cutting tools, drive geometries, and machining strategies. Then, the NC process parameter-driven characteristic of similar feature is revealed from the perspective of machining geometry, machining precision of the feature, and cutter geometry. Moreover, an NC process reusability assessment approach of similar pocket/subpart is presented using the pocket's medial axis transform. Finally, the NC machining process inheritance mechanisms are explored to implement the NC machining process reuse automatically and efficiently. A prototype system based on CATIA has been developed to verify the effectiveness of the proposed approach. Highlights: A feature-based parameter-driven model to guide NC process reuse is established. The NC process parameter-driven characteristic of similar feature is revealed. An NC process reusability assessment approach of similar pocket/subpart is proposed. We extend feature-based NC process reuse to a greater granularity of subpart.